Molecular Characterisation of Haemoglobin constant spring and Haemoglobin Quong Sze with a combine-amplification refractory mutation system - Wee, Y.C.; Tan, K.L.; Chua, K.H.; George, E.; Tan, J.A. (2009)
BACKGROUND: The interaction of the non-deletional Î±(+)-thalassaemia mutations Haemoglobin Constant Spring and Haemoglobin Quong Sze with the Southeast Asian double Î±-globin gene deletion results in non-deletional Haemoglobin H disease. Accurate detection of non-deletional Haemoglobin H disease, which is associated with severe phenotypes, is necessary as these mutations have been confirmed in the Malaysian population. METHODS: DNA from two families with Haemoglobin H disease was extracted from EDTA-anticoagulated whole blood and subjected to molecular analysis for Î±-thalassaemia. A duplex polymerase chain reaction was used to detect the Southeast Asian Î±-globin gene deletion. Polymerase chain reaction-restriction fragment length polymorphism analysis was then carried out to determine the presence of Haemoglobin Constant Spring and Haemoglobin Quong Sze. A combine-amplification refractory mutation system protocol was optimised and implemented for the rapid and specific molecular characterisation of Haemoglobin Constant Spring and Haemoglobin Quong Sze in a single polymerase chain reaction. RESULTS AND CONCLUSIONS: The combine-amplification refractory mutation system for Haemoglobin Constant Spring and Haemoglobin Quong Sze, together with the duplex polymerase chain reaction, provides accurate pre- and postnatal diagnosis of non-deletional Haemoglobin H disease and allows detailed genotype analyses using minimal quantities of DNA.